Inequalities in rates of renal replacement therapy in England: does it matter who you are or where you live? - Judge, A; Caskey, F; Welton, N; Ansell, D; Tomson, C; Roderick, P; Ben-Shlomo, Y (2012)
UNLABELLED: Introduction. This study explores the geographical variation in renal replacement therapy (RRT) incidence and prevalence after adjusting for general population socio-demographics, renal unit treatment patterns and travel times. METHODS: The UK Renal Registry provided data on all patients in England commencing RRT in 2007 and receiving RRT on 31 December 2007. Multilevel Poisson regression models were constructed separately for incidence and prevalence. Geographical Information Systems software enabled estimation of road travel times and renal unit catchment areas. Small area estimates of RRT prevalence were produced for all 354 local authority districts. RESULTS: Adjusted RRT incidence rates were 1.4 (95% confidence interval 1.2-1.6) times higher in the most deprived areas and 1.7 (1.5-2.0) and 1.5 (1.3-1.7) times higher in areas with most Black and South Asian inhabitants (10+%), respectively. The proportion of a centre's patients on haemodialysis or transplanted were positively associated with RRT incidence (not prevalence); numbers of satellite units were negatively associated with RRT incidence (not prevalence). While only 3% of patients lived >30 min from a dialysis unit, there was an effect of travel time on RRT rates; individuals living 45+ min from a dialysis unit were 20% less likely to commence or receive RRT than those living within 15 min (Ptrend=0.36 and Ptrend<0.001, respectively). A 4-fold variation in adjusted local authority district RRT prevalence rates could not be explained. CONCLUSION: Expansion of renal unit facilities in England has reduced travel times in most areas though the possibility of inequitable geographic access to RRT persists.